Robustness of SDOF elastoplastic structure subjected to double-impulse input under simultaneous uncertainties of yield deformation and stiffness. (May 2017) - Kanno, Yoshihiro; Yasuda, Keisuke; Fujita, Kohei; Takewaki, Izuru
Abstract: A series of impulse-type inputs has been extensively used to evaluate the critical response of an elastoplastic structure subjected to diverse types of pulse-type inputs, including a near-fault ground motion. In this paper, we consider the critical double-impulse input for a single-degree-of-freedom elastic–perfectly plastic structure, and study effects of structural uncertainties. When the natural frequency (or, equivalently, the stiffness) is fixed, the critical response of the structure does not necessarily decrease as the yield deformation (or, equivalently, the yield force) increases. As the first contribution, we give through investigation of this non-monotonicity property. Moreover, we present a systematic method for finding the worst-case scenario when the yield deformation and the stiffness of a structure assumed to be uncertain simultaneously. Numerical examples are presented to illustrate that the robustness of a structure does not necessarily improve when the yield deformation and/or the yield force is increased. Abstract : Highlights: The critical response of SDOF elastoplastic structure is considered. Monotonicity of the response with respect to structural parameters is discussed. A method for assessing robustness of the structure is presented. The presented method does not require any approximation. Increase of yield deformation does not necessarily imply robustness improvement.